BENTUK LAPORAN DAN TUGAS PENGAMBILAN KEPUTUSAN DENGAN MENGGUNAKAN INFORMASI KEUANGAN: SUATU INVESTASI EKSPERIMEN LABORATORIUM - RAFDINAL RAFDINAL; NUR INDRIANTORO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2000)
The technology of compugraphy that can result in and present the accounting information in the graphic form of all kinds is one presentation alternatives from the traditional table form (Ives, 1982). The presentation form change and information quantity is one of the basic options to increase the decision maker's performance (Libby 1981, p. 101). The variable of decision maker's performance is implied by the accurateness of the response and time period. The approach use to find the increase of decision maker's performance is laboratoraty experiment and Manova (multivariance analysis of variance) is used to analyze the discrepancies. There are two independent variables. The variable of presentation form is developed into four kinds adopted by Davis (198) i.e. table form, block diagram, line diagram and pie diagram. Variable of decision maker's task is adopted from the study of Hard and Vanecek (1991): accumulation, treatment, estimation, projection. The subjects of this study are the postgraduate students of Gadjah Mada University, consisting of the department of Management Magister Manajemen (MM) and the department of Science Magister (MSi) students. The subjects analyzed are 204 students (MSi and MM are 128 and 86 students respectively) obtained from the total subjects of 214 students. The result of the study shows that there are differences of decision maker performance in using financial statement affected by interaction among presentation forms and the deccision maker task. The result supports the study by Davis (1989) who found that question answered and the presentation form have interactive influence on the performance, and there is no best presentation form have interactive influence on the performance, and there is no best presentation in all circumtances. In other word, presentation form will result in the decision maker performance in different tasks, and it is also true in the opposite way.